Feminisasi Kemiskinan dalam Kultur Patriarki - Arjani, Ni Luh (Jurnal Studi Jender SRIKANDI; Vol. 6, No. 1 Januari 2007)
Nowaday, the amount of the poor people generally in Indonesia and particularly in Bali is still so high. Most of this poverty condition can be fall by the woman. It is not only economic poverty, but also multidimensional poverty such as the limitation of access in education, politic, economy, information, healthy, etc.The poverty feminization relates with the patriarchy culture which still develops in the society. Because of this culture mainly puts the woman in subordinate, the most marginal and the most discrimination position. Therefore, the woman poverty has more specific character which needs a special handling for example by using poverty prevention approach with gender perspective